The best of enemies [large type] - Johnstone, William W.; Johnstone, J. A. (A Trace & Chaw western, 2026)
"Introducing Trace and Chaw: a pugnacious pair of Civil War veterans who nearly killed each other in battle, but lived to fight another day. . . together. They met in a bloodbath. Two demons in uniform caught in the middle of one hell of a war. Private Chaw Dagworth, the Rebel, liked chewing tobacco and fighting blue-bellied Yanks. Private Fullcup Trace, the Yankee, hated Southerners, especially ornery cusses like Chaw. But when the smoke cleared after the Battle of Deadeye Gap, the Blue and the Gray of their uniforms didn't matter anymore. Both were stained blood red. And both were the last men standing. . . . This was the beginning of a beautiful friendship. Now that the war's over, Trace and Chaw travel the West together, taking on odd jobs. They're handy with six-guns and gut-shredders, fond of women and liquor, and always ready to raise hell. Somehow, the unlikely partnership works-until Trace and Chaw sign up with a freighting company run by a beautiful woman. They end up caught in the crossfire between a group of wealthy mine owners from back East-who want to gain ownership of all the small claims and control the freight routes, as well-and the small-claim owners trying to hold out. Like it or not, Trace and Chaw are stuck in the middle of another war. This one's going to be every bit as bloody-and may be their last. . . ."--